Eksplorasi Ethnomatmatika pada Masjid Kampus As-Su’ada Universitas NU Kalimantan Selatan Ditinjau dari Aspek Geometri dan Kaitannya Terhadap Pembelajaran: Exploring Ethnomathematics at South Kalimantan NU University's As-Su'ada Campus Mosque, based on Geometry Perspective and Its Relationship to Learning Activity - Muslim, Azis; Septiani, Rizki Iswi; Herson, Rizqa Firdaus; Dasyalami, M Gilang (Nusantara Journal of Education and Social Science, 2024)
This research aims to explore the cultural site of the Masjid Kampus As-Su’ada Universitas NU Kalimantan Selatan in terms of geometric aspects and its relationship to mathematics learning, especially geometry. The research method used was qualitative with a realist ethnographic approach. The data collection technique is exploration through observation and interviews. The analysis technique in this research is through source collation, namely clarifying the results of observations by interviewing informants. The research results show that the Masjid Kampus As-Su'ada has many geometric shapes on the exterior and interior of the mosque. The geometric shapes contained in it include plane geometry (circle, square, rectangle, triangle and ellipse), solid geometry (pyramid, block, prism) and modified geometry (half tube, truncated pyramid and elliptical approach). Lessons that can be carried out include case studies of mosque roofs, study tours identifying mosque geometric shapes, and determining the area of the building.